Analysis and modeling of standalone wind driven doubly fed induction generator - Bhardwaj, Prerak; K, Vijayakumar (International Journal of Engineering and Technology, 2018)
This paper briefly enlightens on the analysis and modeling aspects of the standalone operation of doubly fed induction generator (DFIG) based wind energy conversion system (WECS). The DFIG in WECS is controlled via a single converter on the rotor terminals. The battery at the converter terminal fulfills the active/reactive power demand of the load. Whereas, the incorporation of the speed estimation technique makes the WECS free from the complexities associated with the speed sensors, thus provide a robust and reliable operation. The control technique used is simple and based on controlling the stator voltage and frequency by their comparison with a reference voltage and frequency using a simple PI controller. The supportive results for the analysis and modelling has been presented for a 7.5 kW wound rotor induction generator in MATLAB/Simulink environment.